Bacterial Load on the Surface of Amniocentesis Operators with or without Long-Sleeved Surgical Gowns: A Prospective Cohort Study - Jinyu Wang; Ying Song; Lingling Sun; Xijing Liu; Fan Zhou; Qianying Zhao; Jing Wang; Xuemei Zhang; Mei Yang; Dan Xie; Ting Hu; Shanling Liu (IMR Press, 2024)
Background: There is currently no specific requirement for operator's attires performing amniocentesis, especially for repetitive amniocenteses. We investigated the contamination status on the surface of operators with or without long-sleeved surgical gowns during repetitive amniocenteses to examine whether they are different. Methods: In a prospective cohort study, consecutive samples were collected from the surface of amniocentesis operators with short-sleeved scrubs (bare arms) or with long-sleeved surgical gowns on 4 sites (including the left and right proximal medial forearm, and the left and right ventral wrist). There were 7 time spots during each sampling period. Results: The highest colony count among all plates was 65 colony forming units (cfu)/plate. We observed 85.3% (382/448) and 65.1% (255/392) plates with 0 colony count from operators with bare arms and in surgical gowns, respectively. Moreover, the bacterial load of the group with surgical gowns had an increasing trend with time while the other group showed a contrary trend. Conclusions: All colony counts observed were within the hygiene specification of the National Health Commission of China. Instead of attires, other measures with high-quality evidence including surveillance of hand hygiene and control of indoor air bacterial load should be given more attention.